Dietary intakes of adolescents from food insecure households: analysis of data from the 6th (2013-2015) Korea National Health and Nutrition Examination Survey - Nakitto, Mariam; Asano, Kana; Choi, Injoo; Yoon, Jihyun (Nutrition Research and Practice, 2017)
This study aimed at evaluating the dietary intakes of Korean adolescents affected by food insecurity, in comparison with those who were food secure. The study used one day 24-hour dietary recall data from the 6th Korea National Health and Nutrition Examination Survey. The study subjects consisted of 1,453 adolescents of whom 695 were middle school-aged and 758 were high school-aged. Food security status was assessed using the 18-item questionnaire. Nutrient intake was evaluated in terms of nutrient density, insufficient intake, and excessive intake for selected nutrients, in addition to meeting the appropriate range for total energy intake and energy intakes from carbohydrate, sugar, protein, fat, and saturated fatty acids. Food intake was evaluated in terms of food group servings and dietary diversity score (DDS). The percentages of food insecurity were 11.1% for middle school-aged adolescents and 16.8% for high school-aged adolescents. Food insecure middle school-aged adolescents had higher intake of carbohydrate (P = 0.006) but lower intake of fat (P = 0.010) and saturated fatty acids (P = 0.005) than their food secure counterparts although the intake of both groups was in the recommended ranges. Nutrient intake among high school-aged adolescents was generally similar regardless of food security status. Both food secure and insecure adolescents showed insufficient intake of vitamin A, vitamin C, and calcium, and excessive sodium intake. They additionally had low prevalence of meeting appropriate intake ranges for energy, carbohydrate, and sugar. Food intake in terms of food group servings and DDS was also similar regardless of food security status among both age groups, with low intakes of foods from fruit and dairy groups. Except for a few nutrients among the middle school-aged adolescents, dietary intakes among Korean adolescents did not differ by food security status in this study.
Keywords: Nutrition surveys; Food supply; Adolescent